Leishmaniasis in Greece: Prospects of transitioning to a One Health surveillance system - Emmanouil Alexandros Fotakis; Dimitris Papamichail; Sofia Boutsini; Eleni Patsoula; Takis Panagiotopoulos (One Health, 2024)
Leishmaniasis is a high burden neglected disease in the Mediterranean ecoregion, lacking surveillance attention. We aimed to provide an overview of the state of leishmaniasis surveillance in Greece, investigating the prospect of transitioning to a One Health surveillance system.We conducted a narrative review describing human and animal leishmaniasis data from Greece, including entomological findings. Through a separate review process, we describe the current leishmaniasis surveillance system pertaining to humans, animals, vectors and the environment. Additionally, we distributed likert-scale questionnaires to key informants, capturing expert-view on the necessity, existing levels and barriers of OH leishmaniasis surveillance in Greece. We identified key system strengths, weaknesses, opportunities and threats respective to a OH transition through SWOT analysis.Greece is endemic for zoonotic visceral leishmaniasis (VL) and canine leishmaniasis (CanL), displaying an increasing VL trend in recent years and high national Leishmania seroprevalence rates in dogs (range: 13.8–23.4 %). Mandatory leishmaniasis notification in humans and animals, human case-based investigations, and active case finding activities in stray dogs, comprise valuable system components of high OH operational relevance. Conversely, the existing CanL surveillance governance and the lack of systematic entomological surveillance constitute important drawbacks. Moreover, the current context of public health and animal health financial constraints in Greece may impede a strategic OH transition in leishmaniasis surveillance. On the contrary, Greece's OH experience in West Nile Virus surveillance in conjunction with leishmaniasis-expert consensus on the necessity of OH surveillance and key barriers to its realization, compose important transition opportunities.Despite shortfalls in human, animal and vector surveillance, existing system characteristics, structures and practices comprise a promising basis for developing OH cross-sectoral leishmaniasis surveillance activities in Greece.